Taking a Stance: Teacher Researchers’ Historical and Political Positioning - Elizabeth Currin (Impacting Education, 2020)
With teacher walkouts and other forms of protest on the rise, EdD programs are beginning to frame practitioner-scholars’ work as activism. The purpose of this article is to explore and complicate that trend by interpreting data from oral history interviews with three long-term teacher researchers, alongside shifting historical scholarship on civil rights activism. Each participant cites civil rights activism as an inspiration and positions the rise of neoliberal education reform as a backlash to the 1960s that threatens the so-called teacher research movement. However, historians challenge the dominant narrative of the 1960s, highlighting behind-the-scenes conservative activism that did not garner the same media attention as liberal marches and boycotts. Consequently, while the participants’ stories offer abundant insight for practitioner-scholars as well as for the teacher educators who guide them, this article ultimately argues EdD activists should take a schoolhouse-to-statehouse approach.